If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Xy + -11 = 15 Reorder the terms: -11 + yX = 15 Solving -11 + yX = 15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + yX = 15 + 11 Combine like terms: -11 + 11 = 0 0 + yX = 15 + 11 yX = 15 + 11 Combine like terms: 15 + 11 = 26 yX = 26 Divide each side by 'X'. y = 26X-1 Simplifying y = 26X-1
| (1/7x^4)-(y-1) | | f(x)=(x+5)(x^2-4) | | Log(x+3)6=1 | | -6+12t=-24 | | log(6x+8)=1+log(x-3) | | 6t^2-12t+14=0 | | 9x^2-45+56=0 | | =3y+2y+7+y | | 0.3+0.2c=8.1 | | 6t^2-12t=14 | | 13p=201.50 | | 15g= | | g^2+5g-24=0 | | 3w^2(w+l)=w(w-2) | | 6x-22=2 | | 6x+14=-5x-8 | | -7+2x=-15 | | -17=10+2m | | H=-10t^2+20t+3 | | Sec^2x=2 | | 2(n+2)=5n+2 | | -12(1+5p)=2(8p+14)+36 | | 0.4x-4=5.6 | | 2*3/7(x-2) | | 6(1-5a)=66 | | 7k^2-2k-12=0 | | (5c^6d^2-3d^3)(-4c^5d)=0 | | 145-5x=y | | -5b-5-(-8)b= | | 0.03x+0.7=1.6 | | 51+4x=47 | | 7(n-3)=42 |